Ubiquity of ToxA and absence of ToxB in Australian populationsof Pyrenophora tritici-repentis - Antoni, E.; Rybak, K.; Tucker, Madeline; Hane, J.; Solomon, P.; Drenth, A.; Shanka, M.; Oliver, Richard (CSIRO Publishing, 2010)
Pyrenophora tritici-repentis, the causal organism of the necrotrophic foliar wheat disease tan spot [alsoknown as yellow (leaf) spot in Australia] is an important disease in Australia and in many parts of the world. NorthAmerican isolates of the pathogen have been shown to produce combinations of three host-specific toxins, ToxA, ToxBand ToxC. Each toxin interacts with a host sensitivity locus, respectively Tsn1, Tsc2 and Tsc1. The virulence of anisolate is partially correlated with the presence of these toxins and resistance in the host is associated with absence ofthe sensitivity loci. Breeding for resistance to tan spot can, therefore, be aided by knowledge of the prevalence ofthe toxin-encoding genes in local pathogen populations. Two of the toxins, A and B, are encoded by known genesand molecular tests for the genes have been developed. We screened a diverse collection of 119 tan spot isolatescollected between 1984 and 2008 and from all affected regions of Australia (Queensland, New South Wales, Victoriaand Western Australia). In all cases, the gene for ToxA was present and the gene for ToxB was absent. Theimplications for resistance breeding and epidemiology of the disease are discussed. We also define a diagnosticmolecular marker for P. tritici-repentis.